Allium elifadae (A. sect. Codonoprasum, Amaryllidaceae), a unique new species from Taurus Mountains/Türkiye - Eker İsmai̇l (Phytotaxa, 2024)
Allium elifadae Eker, a new species in sect. Codonoprasum, is described and illustrated from Adana, Türkiye. It is a quite isolated species, showing some relationships with A. glumaceum Boissier & Haussknecht, from which differs in several morphological features, regarding the bulb tunics, leaves, inflorescence, spathe valves, perigone, stamens and ovary. Its morphology, ecology, distribution, conservation status and taxonomic relationships are examined.